Review of uterine rupture at Paropakar Maternity and Women’s Hospital - Uprety, Iccha; Baral, Gehanath; Shrestha, Shreena (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the case profile of uterine rupture. Methods: Retrospective descriptive study from in-patient record file during two years period. Results: Incidence of uterine rupture recorded was 72 per hundred thousand deliveries (1 in 1390), 25% had ruptured uterus antepartum and 60.7% had live baby. Conclusions: Scarred uterus was the commonest risk factor for rupture uterus and antepartum rupture is not uncommon.